Fungsi WHO Dalam Penanganan Pandemi Covid-19 dan Dampaknya Bagi Hak Asasi Manusia - Janri Jacob Bakarbessy (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The World Health Organization (WHO) is one of the United Nations agencies that acts as the international public health coordinator. The function of the World Health Organization (WHO) is to achieve maximum health for all people around the world. But in reality, WHO seems powerless to handle the Covid-19 pandemic and provide protection for human rights.Purposes of the Research: The purpose of this study is to see and study the implementation of WHO's function in mitigating the Covid-19 pandemic and its impact on human rights.Methods of the Research: The research method in this writing uses the type of research "analytical prescriptive", meaning that the data found is then analyzed and discussed based on the theoretical framework and thoughts of several experts so that the results can only be described to help draw conclusions with suggestions. The technique of collecting legal materials through literature study and qualitative analysis techniques.Results of the Research: The results show that WHO, which was founded on April 7, 1948, has been mandated in the provisions of Articles 57 and Article 63 of the United Nations Charter, is a world health organization that aims to ensure that all people are guaranteed health and well-being on a universal scale. WHO acts as health coordinator in health emergencies. In carrying out the WHO function in handling the Covid-19 pandemic, at first the outbreak of the Covid pandemic was considered slow and the provision of health services was discriminatory. With the lack of anticipation and the WHO's initiative to issue policies to break the chain of the spread of Covid-19, this has greatly impacted countries, health workers and communities around the world, especially restrictions on human rights in the economic, social and cultural fields.